Diffusion of Hydrogen in Steel by Electron Irradiation - Larionov V. V. Vitaliy Vasilyevich; Tyurin Yu. I. Yuri Ivanovich; Nikitenkov N. N. Nikolai Nikolaevich; Dolgov A. S. (Plasma, Microwave, Ion, Electron and Isotope Technologies, 2015)
Title screen